AKTUALISASI MANAJEMEN SUMBER DAYA MANUSIA PADA INSTITUSI PENDIDIKAN TINGGI ‘’X’’ DI KOTA AMBON - ABDUL HARIS TAMALENE (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to explain descriptively the practices of human resource management in higher education institutions X in Ambon City which include planning, recruitment and selection, job analysis and job descriptions. This study is a qualitative study with data collection techniques, namely unstructured interviews. The results showed that the practice of human resource management in the higher education institution X in Ambon City had been implemented well according to established procedures (SOP).